The Semantic Dynamics of Bilingual Code-Mixing in Indonesia’s Digital Landscape: A Systematic Literature Review (2015–2025) - Kesmi Veronika Simanjuntak; Selviana Napitupulu (Young Journal of Social Sciences and Humanities, 2026)
The Indonesian digital communication landscape is characterized by massive code-mixing (CM) phenomena reflecting Gen Z's hybrid identity. This study aims to synthesize CM semantic trends on digital platforms (TikTok , Instagram, WhatsApp) for the 2015-2025 period using Geoffrey Leech's seven types of meaning framework. Employing a Systematic Literature Review (SLR) based on PRISMA 2020 protocols, 25 high-quality articles (average MMAT score of 82%) were thematically analyzed. Findings indicate that CM is not a language deficit but a Society 5.0 adaptive strategy dominated by connotative (38%) and affective (28%) meanings to build cyber solidarity. Despite its prevalence, a pedagogical gap was identified where 68% of studies ignore social-reflective dimensions and the national curriculum remains laggard in responding to these dynamics. This study recommends a reorientation of digital literacy through contextual semantic modules to bridge language competence disparities in the global era.